Corneal Opacity Induced by Antiglaucoma Agents Other Than Brimonidine Tartrate - Yuka Kasuya; Ichiya Sano; Shinji Makino; Hidetoshi Kawashima (Case Reports in Ophthalmological Medicine)
The aim of this study is to report a patient with corneal opacity that developed after the use of topical antiglaucoma medications other than brimonidine tartrate (BT). An 85-year-old woman presented with corneal opacity and neovascularization in both eyes. A diagnosis of glaucoma was made 20 years previously, and antiglaucoma agents were prescribed (latanoprost, tafluprost, timolol maleate, travoprost, bimatoprost, ripasudil hydrochloride hydrate, and brinzolamide/timolol maleate) for both eyes. Ocular examination revealed semicircular fan-shaped corneal sterile infiltration with neovascularization. Anterior-segment optical coherence tomography (OCT) showed marked corneal opacity and thickened corneal stroma. The topical drugs were discontinued and replaced with 0.1% betamethasone eye drops. Two weeks after topical drugs were discontinued and replaced with betamethasone, the corneal sterile infiltration markedly improved, although the corneal opacity remained across the stromal layer. In addition, corneal opacity, intermixed with separate transparent sections, was observed as a striped shape. OCT showed an improvement of the thickened corneal stroma. Six weeks after the initial visit, the remaining corneal opacity could be seen as a mixture of opaque and nonopaque areas in stripes. The corneal stromal thickness decreased almost back to the normal range, while the area of the corneal opacity remained unchanged. In vivo laser confocal microscopy showed hyperreflective materials with needle-like structures in the corneal stroma. The corneal opacity showed several similarities to the previous reports of the cases treated with BT. Therefore, clinicians should be mindful of a possible development of corneal opacity in patients treated with antiglaucoma medications other than BT.